Acute Tears of the Tibialis Posterior Tendon Following Ankle Sprain. (July 2017) - Jackson, Lyle T.; Dunaway, Linda J.; Lundeen, Gregory A.
Background: Traumatic tears of the tibialis posterior (TP) tendon following an ankle sprain are rare. The purpose of this study was to report our case series of TP tendon tears following an ankle sprain. Methods: Patients with persistent TP tendon pain after an ankle sprain were retrospectively identified over a 4-year period and reviewed. A comparison of magnetic resonance imaging (MRI) interpretations by a radiologist and surgeon was made. Patients failing conservative management underwent operative repair of the TP tendon tear and concomitant pathology. Failure of the index surgery was defined as TP tendinosis, which was treated with excision and flexor digitorum longus tendon transfer. Outcomes were measured with the Foot Function Index (FFI) and American Orthopaedic Foot & Ankle Society (AOFAS) hindfoot scores. Results: Thirteen patients were found to have a TP tendon tear following an ankle sprain. The incidence for TP tears with sprains presented to our clinic was 1.04%. MRI identified TP tendon pathology in 4 patients by a radiologist review and in 11 patients by a surgeon review. The most common concomitant pathology was a talar osteochondral defect in 13 of 13 patients and ligament instability in 12 of 13 patients (5/13 lateral, 3/13 medial, 4/13 multidirectional instability). Four of 13 patients failed the index surgery. Of the 9 remaining patients, 4 had clinical follow-up at an average of 4.6 years postoperatively. The average FFI subscale scores were the following: pain, 40.4; disability, 28.9; and activity, 23.6. The average AOFAS hindfoot score was 68.8. Conclusion: Despite being rare, a TP tendon tear should be included in the differential diagnosis for persistent medial-sided pain following an ankle sprain. MRI findings can be subtle. Associated pathology was very common and likely confounded the diagnosis and outcomes. Patients should be counseled on the possibility of poor outcomes and long-term pain. Level of Evidence: Level IV, case series.